Empowering Forms. Hegel’s conception of ‘form’ and ‘formal’ - Ficara, Elena (Hegel, Logic and Speculation)

Hegel and Priest on Revising Logic - Ficara, Elena (Graham Priest on Paraconsistency and Dialetheism)

Hegel on the Naturalness of Logic - Ficara, Elena (Argumenta)

Finite-control-set model predictive control for a permanent magnet synchronous motor application with online least squares system identification - Hanke, Sören; Peitz, Sebastian; Wallscheid, Oliver; Böcker, Joachim; Dellnitz, Michael (2019 IEEE International Symposium on Predictive Control of Electrical Drives and Power Electronics (PRECEDE))

Stator flux-based field-oriented position-sensorless control of permanent magnet synchronous motors with limited parameter knowledge - Wallscheid, Oliver; Shafiq, Muhammad Saad; Böcker, Joachim (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE))

Hierarchical model predictive speed and current control of an induction machine drive with moving-horizon load torque estimator - Wallscheid, Oliver; Ngoumtsa, Etienne Florian Bouna; Böcker, Joachim (2019 IEEE International Electric Machines & Drives Conference (IEMDC))

Continuous-control-set model predictive control with integrated modulator in permanent magnet synchronous motor applications - Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim (2019 IEEE International Electric Machines & Drives Conference (IEMDC))

Improved Fusion of Permanent Magnet Temperature Estimation Techniques for Synchronous Motors Using a Kalman Filter - Gaona, Daniel Efren Erazo; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Industrial Electronics)

The Role of Prices Relative to Supplemental Benefits and Service Quality in Health Plan Choice - Bünnings, Christian; Schmitz, Hendrik; Tauchmann, Harald; Ziebarth, Nicolas R. (Journal of Risk and Insurance)

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (HCII 2019)
This paper explores Finnish, German and Swedish older adults’ perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults’ perception of the future use of welfare technology or care robots. A qualitative approach with focus group discussions was employed, followed by thematic analysis. The results are presented in four overall themes: the impact on daily life for older adults and professional caregivers, codes of practice and terms of use, dissemination of information and knowledge, and conditions for successful implementation. There were significant differences in the informants’ attitudes toward and knowledge about care robots. However, the informants’ attitudes appeared to change during the focus groups and in general, became more positive. Authentic needs, which care robots could support, refer to independence, safety and security, and the ability to manage or ease daily life or working life. The results suggest that older adults, after receiving relevant information, were open to the idea of being supported by care robots in their daily lives.
Keywords: Care robots; Older adults; Implementation; Information; Perceptions; Welfare technology

Computer-Aided Design and Optimization of an Integrated Transformer with Distributed Air Gap and Leakage Path for an LLC Resonant Converter - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. 34th IEEE Applied Power Electronics Conference (APEC))

Computer-Aided Design and Optimization of an Integrated Transformer with Distributed Air Gap and Leakage Path for LLC Resonant Converter - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim; Jungwirth, Herbert; Schmidhuber, Michael (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Novel Current Measurement Concept for Half Bridge Topologies based on simple-to-implement Digital Current Observer - Ahmad, Mohsin Ejaz; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

LCC Resonant Converter for Piezoelectric Transducers with Phase Shift Control - Bolte, Sven; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Bidirectional Resonant Converter with Integrated Magnetics for On-Board Chargers - Bolte, Sven; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

Interleaved Active Clamp Forward Converters as Single Stage On-Board DC-DC Converters for EVs – an Accurate Model and Design Considerations - Rehlaender, Philipp; Grote, Tobias; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A PCB-Integrated Winding Using a Litz Structure for a Wireless Charging Coil - Rehlaender, Philipp; Grote, Tobias; Tikhonov, Sergey; Njiende, Hugues; Schafmeister, Frank; Böcker, Joachim; Thiemann, Peter (Proc. 21st European Conference on Power Electronics and Applications (EPE-ECCE Europe))

Analytical Topology Comparison for a Single-Stage On-Board EV-Battery Converter - Rehlaender, Philipp; Grote, Tobias; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

Current measurement circuit for TCM-PFC - Pohlmann, Robert; Schafmeister, Frank

Representative Sample Extraction from Spray Flames for SMPS and HR-TEM Measurements - Tischendorf, Ricardo; Bieber, M.; Kneer, R.; Schmid, Hans-Joachim
Keywords: FSP; nanoparticle synthesis; in situ measurements

Experimentelle Charakterisierung von Eisenoxid-Nanopartikeln aus Sprayflammen mit koaxialer Zweistoffzerstäubung - Tischendorf, Ricardo; Schmid, Hans-Joachim

PhASAR: An Inter-Procedural Static Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric (Proceedings of the 25th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS 2019), Held as Part of the European Joint Conferences on Theory and Practice of Software (ETAPS 2019))

Dynamische Simulation reaktiver Absorptionsprozesse zur Entwicklung modellbasierter Werkzeuge zur Vermeidung von Vor- und Notfallsituationen in der Industrie - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny

Logik im Logischen Empirismus - Peckhaus, Volker (Der Wiener Kreis – Aktualität in Wissenschaft, Literatur, Architektur und Kunst)

Identifikation und Kompensation produktionsbedingter Abweichungen im elektrischen Antrieb von Elektro- und Hybridfahrzeugen - Ott, M.

Self-sealing tool concept for RTM-processes - Stallmeister, Tim; Chalicheemalapalli Jayasankar, Deviprasad; Wang, Z.; Tröster, Thomas

Selbstabdichtendes Werkzeugkonzept für RTM-Prozesse - Stallmeister, Tim; Chalicheemalapalli Jayasankar, Deviprasad; Wang, Z.; Tröster, Thomas

End Group Stability of Atom Transfer Radical Polymerization (ATRP)-Synthesized Poly(N-isopropylacrylamide): Perspectives for Diblock Copolymer Synthesis - Herberg, Artjom; Yu, Xiaoqian; Kuckling, Dirk (Polymers)
Keywords: controlled radical polymerization; atom transfer radical polymerization; end group determination; N-isopropylacrylamide; block copolymerization; smart polymers; temperature sensitive polymers; lower critical solution temperature; ESI-TOF mass spectrometry; ion mobility separation; size exclusion chromatography

Dually Cross‐Linked Supramolecular Hydrogel as Surface Plasmon Resonance Sensor for Small Molecule Detection - Li, Jie; Ji, Chendong; Yu, Xiaoqian; Yin, Meizhen; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Thermoresponsive Catechol Based-Polyelectrolyte Complex Coatings for Controlled Release of Bortezomib - Reis, Berthold; Vehlow, David; Rust, Tarik; Kuckling, Dirk; Müller, Martin (International Journal of Molecular Science)
Keywords: catechol chemistry; poly(caffeic acid); polyelectrolyte complex coatings; thermoresponsive coatings; controlled release; bortezomib; multiple myeloma

Azlactone-functionalized smart block copolymers for organocatalyst immobilization - Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (European Polymer Journal)
Keywords: Organic Chemistry; Polymers and Plastics; General Physics and Astronomy; Materials Chemistry

In vitro evaluation of innovative light-responsive nanoparticles for controlled drug release in intestinal PDT - Mahlert, Laura; Anderski, Juliane; Schoppa, Timo; Mulac, Dennis; Sun, Jingjiang; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
Keywords: Light-responsive polymersPhotodynamic therapyControlled drug deliveryHT-29-MTX cellsIntestinal cancer

Light-Responsive Serinol-Based Polycarbonate and Polyester as Degradable Scaffolds - Sun, Jingjiang; Jung, Dimitri; Schoppa, Timo; Anderski, Juliane; Picker, Marie-Theres; Ren, Yi; Mulac, Dennis; Stein, Nora; Langer, Klaus; Kuckling, Dirk (ACS Applied Bio Materials)
Keywords: light-responsive polymers; biodegradable polymers; polycondensation

Preparation of Light-Responsive Aliphatic Polycarbonate via Versatile Polycondensation for Controlled Degradation - Sun, Jingjiang; Anderski, Juliane; Picker, Marie-Theres; Langer, Klaus; Kuckling, Dirk (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Liberating or indoctrinating? Surveying students’ perceptions of a Womens’ and Gender Studies requirement - Horwath, Ilona; Diabl, Christian (Gender and Education)
This article offers new insight into students’ responses to Womens’ and Gender Studies (WGS) classes by overcoming the self-selection bias hitherto inherent in the field. Exploring the experiences of 1406 students (770 women, 636 men) of a university with a WGS requirement across all study programmes, we examine the prevailing discourses on WGS, participants’ (dis)agreement as well as personal and professional benefits gained through WGS. Additionally, we evaluate the perceived value of WGS for themselves, in society, and of WGS opportunities in higher education. Findings reveal a gender bias regarding discourses, experience, benefit, and value, with 70.1% women and 32.4% men supporting the idea of WGS as a mandatory subject. Women’s support indicates a need for tools to negotiate gender issues, while men’s resistance serves to defend male privileges. We conclude that a requirement of WGS classes amplifies the potential for both – resistance and change.
Keywords: Education policy; equality; higher education; critical pedagogies; gender mainstreaming; curriculum

DEVELOPMENT OF A CYBER-PHYSICAL SIMULATION ASSISTANCE SYSTEM FOR PARTIALLY AUTOMATED OPTIMIZATION OF THE EXTRUSION PROCESS - Terhechte, Johannes; Berscheid, Anna Lena; Horwath, Ilona

Einleitung: Cyborgs revisited: Zur Verbindung von Geschlecht, Technologien und Maschinen - Berscheid, Anna Lena; Horwath, Ilona; Riegraf, Birgitt (Feministische Studien)

Phenomena of forming and failure in joining hybrid structures – Experimental and numerical studies of clinching thermoplastic composites and metal - Vorderbrüggen, Julian; Gröger, Benjamin; Kupfer, Robert; Hoog, Arne; Gude, Maik; Meschut, Gerson (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Investigations on a material-specific joining technology for CFRP hybrid joints along the automotive process chain - Vorderbrüggen, Julian; Meschut, Gerson (Composite Structures)

Plastic droplet welding: bond strength between plastic freeforming structures and continuous fiber-reinforced thermoplastic composites - Moritzer, Elmar; Hirsch, André; Heim, H.P.; Cherif, C.; Truemper, W. (Welding in the World)
Plastic freeforming (PF) is an additive-manufacturing process for producing three-dimensional plastic parts based on 3D CAD data by applying plastic droplets in layers. This process is used to produce customer-specific and complex geometries (prototypes and small series) on organic sheets. A comparable serial process is the injection of a second component onto organic sheets by injection molding. A sufficient bond between the PF structure and the organic sheets is of particular importance for each application. If this is not guaranteed, the composite system cannot withstand the mechanical load and fails. The force exerted on the system can no longer be transmitted between the PF structure and the organic sheet. The organic sheet is made of glass fiber-reinforced polypropylene (PP). The connection between the organic sheet and the PF structure is achieved by welding the molten polymer droplets and the surface of the organic sheet. The PF structures are made of PP to ensure sufficient compatibility with regard to the weldability of the components. The processing of PP in the PF process is a challenge because PP is a semicrystalline material. The shrinkage of semi-crystalline materials is significantly higher compared to amorphous materials. Due to the layered structure of the components, the shrinkage of the individual layers results in undesired warpage. The adhesive strength between the organic sheet and the PF structure is investigated by determining the bending strength in the 3-point bending test. The investigations include an optimization of the process parameters to maximize the adhesive strength. The experimental investigations show that an increase of the nozzle and build chamber temperature leads to a higher adhesive strength. In further investigations, the temperature of the nozzle shows no significant influence on the surface temperature despite the expected heat radiation. The surface temperature is almost only dependent on the temperature of the build chamber.

Development and Modeling of Design and Process Guidelines for FDM Structures for the Partial Reinforcement of Hybrid Structures - Moritzer, Elmar; Hirsch, André; Bürenhaus, Franziska Isabelle (AIP Conference Proceedings)
The mechanical properties of thin-walled plastic components are limited. One approach to improve the strength or stiffness of these components is to reinforce the thin-walled areas with an individually adapted Fused Deposition Modeling structure. Fused Deposition Modeling (FDM) is one of the most commonly used additive manufacturing processes. This process is characterized by the deposition of a fused, thermoplastic filament. Depending on the form of the reinforcement structure, the resulting hybrid structure should show higher strength or stiffness. The objective of the project is to determine constructive design and process guidelines for FDM structures. The FDM structure is to be used as a partial reinforcement for lightweight components and be adapted to the respective load conditions. Because of the lightweight application, the FDM structure should also have the lowest possible weight. The optimization of the FDM parts for different load cases is realized by adapting the design parameters. These parameters influence the layer generation and therefore also the inner structure of the FDM parts. In preliminary studies, the manufacturing restrictions of the FDM process are defined. The specimens are manufactured based on the Design of Experiments. To determine the static strength properties, different tests (tensile, compression, flexural, torsion and impact) are carried out. The investigations show that the filling strategy affects the mechanical properties. As a result of the investigations, design and process guidelines for the FDM structures are established according to the load conditions.

A Method to Evaluate the Process-Specific Warpage for Different Polymers in the FDM Process - Schöppner, Volker; Schumacher, C.; Fels, C. (AIP Conference Proceedings)
Additive manufacturing processes, like the Fused Deposition Modeling (FDM) process, do not need product-specific tools and create parts directly from the CAD data. In the FDM process, the semi-finished product, a wire of a thermoplastic polymer, is melted and forced through a nozzle. The continuous positioning of this nozzle allows the polymer to weld together strand by strand and layer by layer to produce a component. Because no mold is used in the FDM process, no holding pressure can be generated as in injection molding processes, in which the holding pressure is used to minimize the shrinkage and warpage of the part. In the FDM process, the part is generated in an ambient pressure environment. Each strand cools down and shrinks separately. This causes residual stresses in the part that can lead to major warpage and a complete stoppage of the process. This is the main reason why the material selection in the FDM process is restricted in comparison to conventional polymer processing technologies. In this paper, the warpage of different polymers is quantified as a criterion for evaluating the processability of polymers in the FDM process. Due to the process principle, the part properties in the FDM process are mainly influenced by the machine quality and the data processing, so that it is difficult to test a material for FDM independently of the machine and the data processing. Considering these influences, a custom-built specimen is created to test and quantify the warpage of different types of blended and reinforced polyamide 6. Considering the experimentally investigated warpage, the materials can be evaluated and the warpage can be related to the shrinkage investigated in pvT measurements. This procedure allows the machine- and process-independent rating of the processability in terms of warpage for different materials. Alongside other criteria, this is a necessary step to develop new materials with good processability in the FDM process.

Rissausbreitungsmechanismen in FDM-Verstärkungsstrukturen unter dynamischer Beanspruchung - Moritzer, Elmar; Hirsch, André; Paulus, S.
Das Fused Deposition Modeling (FDM) ist ein etabliertes additives Fertigungsverfahren zur Her-stellung von thermoplastischen Kunststoffbauteilen. In dem vorliegenden Beitrag sind FDM-Verstärkungsstrukturen aus dem Material Ultem 9085 dynamischen Langzeituntersuchungen un-terzogen worden. Dabei wurde die innere Struktur der Probekörper über eine Parametervariation verändert, sodass anschließend die signifikanten Einflussfaktoren auf die Langzeitfestigkeit un-ter dynamischer Belastung identifiziert und analysiert werden konnten. Mit dieser Vorgehens-weise sollte gleichzeitig eine Optimierung der FDM-Verstärkungsstrukturen hinsichtlich der dy-namischen Langzeiteigenschaften bei Biege- und Druckbelastungen vorgenommen werden. Des Weiteren sind anhand der Probekörper die auftretenden Bruch- und Rissausbreitungsmechanis-men analysiert worden. Anhand der ermittelten Wöhlerkurven kann die Lebensdauer unter dy-namischer Belastung abgeschätzt werden. Außerdem zeigen die Untersuchungen, dass Fehlstel-len durch eine hohe Strangbreite und Überfüllungen im Bauteil für Schwachstellen in den FDM-Verstärkungsstrukturen sorgen, an denen Risse bei Druckbelastung entstanden sind und sich dadurch schneller ausbreiten konnten.

Modellierung und Optimierung leistungselektronischer Konverter mit Halbleitern großer Bandlücke unter Verwendung kalorimetrischer Messverfahren - Bolte, Sven

Untersuchung des Verlustverhaltens eines geregelten und mit optimierten Pulsmustern gespeisten Hochgeschwindigkeits-Antriebssystems - Peter, Klaus
Hochgeschwindigkeitsantriebe kommen unter anderem in Vakuumpumpen, Turboradialverdichtern und Zentrifugen zum Einsatz und zeichnen sich typischerweise durch einen Betrieb mit konstanter Drehzahl über längere Zeiträume aus. Das in dieser Arbeit betrachtete Antriebssystem setzt sich aus einer permanentmagneterregten Synchronmaschine mit magnetgelagertem Rotor, einem LC-Filter, einem Wechselrichter in 2- oder 3-Stufen-Topologie, diverser Sensorik sowie einem Antriebsregler zusammen. In der vorliegenden Arbeit wurden Pulsmusterformen auf viertel- und halbschwingungssymmetrischer Basis ausgewählt und nach relevanten Kriterien wie die Eliminierung niederfrequenter Harmonischer oder die Minimierung des Oberschwingungsgehalts offline-optimiert. Hierzu wurde eine modifizierte Variante der Partikel-Schwarm-Optimierung verwendet. Ziel war die Substitution der trägerbasierten Dreiecksmodulation durch eine geeignete Modulatorstruktur zur Generierung und Ausgabe offline-optimierter Pulsmuster an den Wechselrichter. Im Verlauf der Arbeit wurde zudem herausgestellt, dass die herkömmliche feldorientierte Reglerstruktur nicht mit den optimierten Pulsmustern kombiniert werden kann, was auf die fehlende Pulssymmetrie und die abweichenden Kurzzeitmittelwerte der Schaltsignale von der Stellspannung im aktuellen Reglertakt zurückzuführen ist. Daher wurde eine modellbasierte Reglerstruktur, die zum Teil steuernden Charakter aufweist, entworfen und implementiert. Durchgeführte Messungen an einem Laststand mit einer Bemessungsleistung von 150 kW ergaben im maximal zulässigen Arbeitspunkt gegenüber der dreiecksmodulierten Pulsweitenmodulation eine Steigerung des Gesamtwirkungsgrads von bis zu 0,6% bei Verwendung eines 2-Punkt-Wechselrichters mit ausgangsseitigem LC-Filter.

Ein Beitrag zur Regelung von Permanentmagnet-Synchronmotoren in Statorflusskoordinaten ohne Rotorlagesensor - Pape, Thorsten

Optical transition between two optical waveguides layer and method for transmitting light - Hammer, Manfred; Förstner, Jens; Ebers, Lena
Die Erfindung betrifft einen optischen Übergang zwischen zwei optischen Schichtwellenleitern. Dazu ist eine Anordnung vorgesehen aus einem ersten optischen Schichtwellenleiter (2) und einem zweiten optischen Schichtwellenleiter (3), wobei der erste optische Schichtwellenleiter (2) und der zweite optische Schichtwellenleiter (3) voneinander verschiedene über ihre jeweilige Länge konstante Dicken (d, r) aufweisen, der erste optische Schichtwellenleiter (2) mit dem zweiten optischen Schichtwellenleiter (3) mittels einer optischen Schichtwellenleiterstruktur (4) verbunden ist, die über ihre gesamte Länge (w) eine Dicke (h) aufweist, die zwischen der Dicke (d) des ersten optischen Schichtwellenleiters (2) und der Dicke (r) des zweiten optischen Schichtwellenleiters (3) liegt. Erfindungsgemäß ist die Dicke (h) der optischen Schichtwellenleiterstruktur (4) über die gesamte Länge (w) der optischen Schichtwellenleiterstruktur (4) konstant. Damit wird eine Möglichkeit für einen effizienten und mit geringen Verlusten behafteten Übergang zwischen zwei optischen Schichtwellenleitern mit unterschiedlicher Dicke bereitgestellt.
Keywords: tet_topic_waveguides

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

'De triomf van de mens’ – kennis in 'Geschiedenis van een berg' - Lammer, Christina (Naar het onbekende: Perspectieven op literatuur, cultuur en kennis)

An Approach for Mapping Periodic Real-Time Tasks to Reconfigurable Hardware - Guettatfi, Zakarya; Platzner, Marco; Kermia, Omar; Khouas, Abdelhakim (2019 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW))

Konstruktionen des Terrors. Zur Hassrede in den Romanen Jenseits von Deutschland von George Tenner und Das dunkle Schiff von Sherko Fatah - Willeke, Stephanie (Hass/Literatur. Literatur- und kulturwissenschaftliche Beiträge zu einer Theorie- und Diskursgeschichte)

„So kommt doch alles noch zum Happy End.“ Sammy Gronemanns zionistische Komödie Der Prozess um des Esels Schatten - Willeke, Stephanie (Zwischen den Sprachen – Mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

Der eingehegte Terrorist? Dorothea Dieckmanns Guantánamo - Willeke, Stephanie (Das Politische in der Literatur der Gegenwart)

Portfolioarbeit als Professionalisierungsgelegenheit - Ballweg, Sandra (Portfolioarbeit im Kontext von Sprachenunterricht. Neue internationale Entwicklungen)

Das Verhältnis zwischen Fremdsprachenerwerbsforschung und Fremdsprachenunterricht - Einführung in das Themenfeld - Ballweg, Sandra; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Theorien und Hypothesen für den L2-Erwerb - Einführung in das Themenfeld - Ballweg, Sandra; Introna, Silvia; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Revealing the intrinsic geometry of finite dimensional invariant sets of infinite dimensional dynamical systems - Gerlach, Raphael; Koltai, Péter; Dellnitz, Michael (arXiv:1902.08824)
Embedding techniques allow the approximations of finite dimensional attractors and manifolds of infinite dimensional dynamical systems via subdivision and continuation methods. These approximations give a topological one-to-one image of the original set. In order to additionally reveal their geometry we use diffusion mapst o find intrinsic coordinates. We illustrate our results on the unstable manifold of the one-dimensional Kuramoto--Sivashinsky equation, as well as for the attractor of the Mackey-Glass delay differential equation.

Materials für inclusive mathematics education - Design principles an practices. - Häsel-Weide, Uta; Nührenbörger, M. (Proceedings of the Third International Conference on Mathematics Textbook Research an Development)

Fördern im inklusiven Mathematikunterricht im Spannungsfeld zwischen gemeinsamen Lernsituationen und gezielter Förderung. - Breucker, T.; Freesemann, O.; Häsel-Weide, Uta; Opitz, E. M.; Nührenbörger, M.; Wittich, C. (Zeitschrift für Heilpädagogik)

Das Zahlenbuch 4. Förderheft - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Das Zahlenbuch. Förderkommentar Lernen zum 4. Schuljahr - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Wille, Matthias, "Gottlob Frege. Begriffsschrift, eine der arithmetischen nachgebildete Formelsprache des reinen Denkens", Springer Spektrum: Berlin 2018 (Klassische Texte der Wissenschaft) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Honerkamp, Josef, "Denken in Strukturen und seine Geschichte. Von der Kraft des mathematischen Beweises", Springer: Berlin 2018 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Borrowing, Code-Switching and Fused Lects: Language Contact and Multilingual Prac-tices from a Socio-Historical Perspective - Ptashnyk, Stefaniya (Dimensionen des sprachlichen Raums: Variation - Mehrsprachigkeit - Konzeptualisie-rung (Schriften zur deutschen Sprache in Österreich))

Mediale (Selbst-)Referenzen in der galizischen Presse des 19. Jahrhunderts: „Gazeta Lwowska“ und „Lemberger Zeitung“ im Vergleich - Ptashnyk, Stefaniya (Mediale Selbstreferenzen)

„Stadtrechte und Stadtrechtsreformationen“. Tagung an der Heidelberger Akademie der Wissenschaften vom 03.04.2019 – 05.04.2019. Tagungsbericht - Ptashnyk, Stefaniya; Falkson, Katharina; Lemberg, Ingrid (HSozKult (online unter https://www.hsozkult.de/conferencereport/id/tagungsberichte-8281))

Jesseph, Douglas M., “Hobbes and the Syllogism”, in: Marco Sgarbi/Matteo Cosci (Hgg.), The Aftermath of Syllogism, Blumsbury Academic: London 2018 (Bloomsbury Studies in the Aristotelian Tradition), 67–81 - Peckhaus, Volker (Mathematical Reviews)

Tieszen, Richard, “Husserl and Gödel”, in: Stefania Centrone (Hg.), Essays on Husserl’s Logic and Philosophy of Mathematics, Springer: Dordrecht 2017 (Synthese Library; 384), 431–459 - Peckhaus, Volker (Mathematical Reviews)

Vanzo, Alberto, “Kant’s False Subtlety of the Four Syllogistic Figures”, in: Marco Sgarbi/Matteo Cosci (Hgg.), The Aftermath of Syllogism, Blumsbury Academic: London 2018 (Bloomsbury Studies in the Aristotelian Tradition), 157–190 - Peckhaus, Volker (Mathematical Reviews)

Lernumgebungen für den inklusiven Mathematikunterricht zwischen reichhaltiger Offenheit und fokussierter Förderung - Häsel-Weide, Uta (Zwischen Persönlichkeitsbildung und Leistungsentwicklung. Fachspezifische Zugänge zu inklusivem Unterricht)

Book Review: Deutsch im 17. Jahrhundert: Studien zu Sprachkontakt, Sprachvariation und Sprachwandel. Gedenkschrift für Jürgen Macha. (Sprache - Literatur und Studien zur Linguistik/Germanistik, Band 46) - Ptashnyk, Stefaniya (Journal of Historical Sociolinguistics, 2/2019 (online))

Vertrauensbildung und Reputationssysteme auf digitalen B2B-Märkten - Ein klassifizierender Überblick - Kilic, Mehmet

Gib anderen dein Zuhause - Eine deskriptive Analyse der Ausbuchungsrate von Inseraten auf Airbnb - Yilmaz, Melih

Conception of a digital Sales Bonus System based on Blockchain Technology - Rodehutskors, Luca Maurizio

Entwicklung eines Frameworks für Geschäftsmodelle im On-The-Fly Computing - Dirksen, Daniel

Worüber sprechen Ihre Kunden? Anwendung und Evaluation von Text Mining auf Online-Kundenbewertungen am Beispiel von Google Maps Reviews - Lo Tauro, Santo Stefan

Haben B2B-Kunden auch Gefühle? Eine semantische Analyse von Online-Kundenbewertungen auf digitalen B2B-Märkten - Post, Hannes

Kreativität in der Wirtschaftsinformatik: Ein systematischer Literaturüberblick von Experiment-Designs - Henke, Lena

Kreativitäts-Experimente in der Wirtschaftsinformatik - Ein systematischer Literaturüberblick - Recker, Davide Pietro

The Digital CV - Ein Literaturüberblick über Onlien-Bewertungen in Online Labor Markets - Meier zu Wickern, Joelle

Eine deskriptive Analyse der Verteilung von Online-Bewertungen auf digitalen B2B-Märkten - Petrovic, Bogoljub

Eine semantische Analyse von Online-Bewertungen auf digitalen B2B-Märkten - Schulte, Tristan Aaron

Entwicklung eines Rahmenwerks zur Evaluation von Geschäftsmodellen zur Entscheidungsunterstützung für Kooperationen mit Startups am Beispiel der Schüco International KG - Golis, Miriam

Feasibility study on the use of Hypermedia/HATEOAS using an example of a RESTful API from the financial services environment based on OpenAPI/Swagger - Brockmeier, Felix Karl

Mechanismen zur Aggregation der Meinungen einer Crowd - Ein klassifizierender Literaturüberblick - Schiller, Leo

The effects of driver variables on online review metrics: A meta-analysis - Selig, Maximilian Julius

Share at all Costs? Ein Literaturüberblick zur Privacy Risk Calculus Theory - Althaus, Maike

Sozioökonomische Implikationen des Sharing Economy Trends - Rohde, Lukas

Reputation in der Sharing Economy - Eine ökonometrische Analyse des Zusammenhangs zwischen Online-Bewertungen und Nachfrage am Beispiel von Airbnb - Bentfeld, Bastian

Stoppt das Sharing? Ökonometrische Untersuchungen zur gesetzlichen Einschränkung von Airbnb - Agethen, Christopher Heinrich

It's a match! - Entwicklung eines Ansatzes zur Identifikation von Cross-Listings auf Airbnb und TripAdvisor - Wegener, Moritz

Do Online Ratings Matter in the Sharing Economy? Analyzing the Impact of Online Ratings on Demand on Airbnb - Gerzen, Gabriele

Möglichkeiten und Grenzen crowdbasierter Ideenbewertung - Ein systematischer Literaturüberblick - Resch, Tim

Externe Stimuli zur Geschäftsmodell-Ideengenerierung: Ein Experimenteller Ansatz - Milder, Christoph

Blätterwald zur Positionierung in akademischen Texten - Karsten, Andrea (Praxishandbuch Schreibdidaktik. Übungen zur Vermittlung wissenschaftlicher Schreibkompetenzen)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas; Mirhosseini, S. Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Alkali Atoms Diffusion Mechanism in CuInSe 2 Explained by Kinetic Monte Carlo Simulations - Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Henkelman, Graeme; Mirhosseini, Hossein (Advanced Theory and Simulations)
Adaptive kinetic Monte Carlo simulation (aKMC) is employed to study the dynamics and the diffusion of point defects in the CuInSe2 lattice. The aKMC results show that lighter alkali atoms can diffuse into the CuInSe2 grains, whereas the diffusion of heavier alkali atoms is limited to the Cu-poor region of the absorber. The key difference between the diffusion of lighter and heavier alkali elements is the energy barrier of the ion exchange between alkali interstitial atoms and Cu. For lighter alkali atoms like Na, the interstitial diffusion and the ion-exchange mechanism have comparable energy barriers. Therefore, Na interstitial atoms can diffuse into the grains and replace Cu atoms in the CuInSe2 lattice. In contrast to Na, the ion-exchange mechanism occurs spontaneously for heavier alkali atoms like Rb and the further diffusion of these atoms depends on the availability of Cu vacancies. The outdiffusion of alkali substitutional atoms from the grains results in the formation of Cu vacancies which in turn increases the hole concentration in the absorber. In this respect, Na is more efficient than Rb due to the higher concentration of Na substitutional defects in the CuInSe2 grains.

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game